2010
DOI: 10.1155/2010/438676
|View full text |Cite
|
Sign up to set email alerts
|

The Epworth Sleepiness Scale: Self‐Administration Versus Administration by the Physician, and Validation of a French Version

Abstract: In a sleep clinic population, the French version of the ESS performed similarly to the English version. However, the systematic underscoring during physician administration may be important to consider in the research setting if questionnaire administration methods are not consistent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(48 citation statements)
references
References 34 publications
1
43
0
4
Order By: Relevance
“…As reported by Kaminska and others, 26 the selfadministered ESS scores were higher than the scores given by the physician. Since this study was interviewer administered the ESS scores resulted might be lower than the self-rated ESS scores of this study sample.…”
Section: Discussionsupporting
confidence: 49%
“…As reported by Kaminska and others, 26 the selfadministered ESS scores were higher than the scores given by the physician. Since this study was interviewer administered the ESS scores resulted might be lower than the self-rated ESS scores of this study sample.…”
Section: Discussionsupporting
confidence: 49%
“…Studies published so far are inconsistent in this matter. It was demonstrated that the results of the ESS questionnaires carried out by physicians differed from those filled unaided (8.3±5.8 vs. 9.4±5.8, p < 0.0001) [15]. On the other hand, Damiani et al showed that the results of the physician-administered ESS were higher than a conventional, self-administered questionnaire (12.09±4.1 vs. 10.37±5.49, p = 0.01) and were stronger correlated apnea-hypopnea index assessed with portable device [16].…”
Section: Discussionmentioning
confidence: 91%
“…Medication tolerability and safety in the two treatment groups were evaluated and compared on the basis of change in alertness and mood on final wakening (Recorded as Visual analog scales), Epworth sleepiness scale 22 score to measure day time sleepiness, other adverse events observed during the study, any clinically significant change in the value of laboratory parameters, vital signs and physical examination during the study compared to baseline.…”
Section: Safety and Tolerabilitymentioning
confidence: 99%